Transmembrane collagens—Unexplored mediators of epidermal‐dermal communication and tissue homeostasis. Issue 1 (17th September 2020) - Nyström, Alexander; Kiritsi, Dimitra
Abstract: Tissue homeostasis is maintained through constant, dynamic and heterogeneous communication between cells and their microenvironment. Proteins that are at the same time active at the intracellular, cell periphery and deeper extracellular levels possess the ability to, on the individual molecular level, influence the cells and their microenvironment in a bidirectional manner. The transmembrane collagens are a family of such proteins, which are of notable interest for tissue development and homeostasis. In skin, expression of all transmembrane collagens has been reported and deficiency of transmembrane collagen XVII manifests with distinct skin phenotypes. Nevertheless, transmembrane collagens in skin remain understudied despite the association of them with epidermal wound healing and dermal fibrotic processes. Here, we present an overview of transmembrane collagens and put a spotlight on them as regulators of epidermal‐dermal communication and as potential players in fibrinogenesis.